Dampak Ketidakharmonisan dalam Rumah Tangga (Studi Kasus Pengadilan Agama Stabat Kelas I-B dalam Perkara Cerai Gugat dengan Nomor Perkara 1350/PDT.G/2023/PA.STB) - Nuryufa Maura; Ahmad Sanusi Luqman (Journal Smart Law, 2024)
Household disharmony experienced by a husband and wife in a divorce case with case number 1350/Pdt.G/2023/PA.STB. begins with the wife's boredom with the husband's behavior which makes the wife feel uncomfortable and insecure. This study aims to determine the factors that cause husband and wife to be disharmonious in the household, then to determine the impact of disharmony in the household in the Divorce Case with Case Number 1350/PDT.G/2023, and to find out how the Religious Court's decision on the divorce case is based on Law Number 1 of 1974 concerning Marriage. The method used in this study is a qualitative research method which is included in the type of field research. This study uses focus group methods, in-depth interviews, and observations in collecting data. There are 4 stages carried out by researchers in analyzing data, namely data collection, data reduction and categorization, data presentation, and verification. The results of this study are about disharmony in the household focusing on various factors that influence husband-wife relationships and their impact on individuals, families, and society. From several prolonged household conflicts, especially in divorce cases with the number 1350/Pdt.G/2023/PA.Stb, which resulted in divorce or the end of the relationship between husband and wife in a marriage bond, this case was decided by the Stabat Religious Court on August 28, 2023 AD, coinciding with the 11th of Shafar 1445 Hijriah by Dra. Siti Masitah, S.H as Chair of the Panel, Drs. Maimuddin and M. Rizfan Wahyudi, S.H, each as Member Judges.